Authenticity and loyalty at heritage sites: The moderation effect of postmodern authenticity. (August 2018) - Yi, Xiaoli; Fu, Xiaoxiao; Yu, Larry; Jiang, Liao
Abstract: Authenticity and postmodern authenticity are often regarded as contradictory, and the two are rarely considered simultaneously by researchers. Taking as research cases two Chinese World Heritage Sites, Kaiping watchtowers in Guangdong province and Yongding earth building in Fujian province, this study constructed a relationship model of perceived authenticity, existential authenticity, and loyalty by examining the effects of tourists' perceptions of the authenticity of tangible and intangible heritage on tourists' existential authenticity and destination loyalty, as well as the relationship between existential authenticity and destination loyalty. Building upon the relationship model, this study further examined the moderating role of postmodern authenticity on the relationship between perceived authenticity and existential authenticity. Results indicated that postmodern authenticity moderates the influence of architectural heritage on existential authenticity: the higher the level of postmodern authenticity, the lower the effect. Theoretical and management implications are discussed. Highlights: The relationship of perceived authenticity, existential authenticity and destination loyalty was further verified. Perceived authenticity exerted a significant effect on destination loyalty. Existential authenticity transmitted positively the effect of perceived authenticity on destination loyalty. Postmodern authenticity moderated the effect of architectural heritage on loyalty through existential authenticity. Postmodern authenticity can be a vantage point to better understand the subjectivity of tourist experiences.